ANALYSIS OF THE EFFECT OF DOWN TIME ON PRODUCTIVITY AT PT. EASTERN PEARL FLOUR MILLS MAKASSAR - Ahmad, Ilham; Saleh, Rahmawati; Rahmaniar, Rahmaniar (Journal of Agriculture, 2023)
Productivity is a comparison between the results achieved (output) with the overall required resources (input) or a comparison between the results achieved with the role of labor per unit time. The purpose of this study was to study Down Time analysis techniques for productivity in a wheat processing company (PT. Eastern Pearl Flour Mills Makassar), which produces wheat flour products of the Gatotkaca, Gunung, Kompas and Gerbang types. Down Time is the amount of time when a tool/machine cannot operate due to failure, but the factory can still operate because there are still other tools/machines that can replace functions so that the production process can still run. Based on the data analysis of the calculation of down time for manpower, it shows that the existence of down time during the process will affect the level of productivity (actual and standard). The value of down time from the calculation of working hours minus work effectiveness results in down time for each production area each month. The manpower down time results from all areas, namely in the area of 0 minutes/month. While the amount of data from the analysis of down time calculations for machines in all areas has a higher number of machine down times, namely in the milling area of 28 hours. And for the lowest results, namely in the area of unloading, cleaning, and packing, it is 0 hours.